2007
DOI: 10.1016/j.bbrc.2007.05.074
|View full text |Cite
|
Sign up to set email alerts
|

Family 18 chitolectins: Comparison of MGP40 and HUMGP39

Abstract: Glycosidase and lectins both bind sugars, but only the glycosidases have catalytic activity. The glycosidases occur among 91 evolved protein families and Family 18 is one of the two chitinases (EC 3, 2.1.14) families. Interestingly, lectins are also in this evolutionary group of Family 18 glycosidase proteins. The proteins belonging to the enzymatically inactive class are referred to as, chitolectins and have a binding site that is highly similar to the catalytic Family 18 enzymes. We present a comparison of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Endogenous animal lectins are extremely diverse, and are organized into many families, including C-type, R-type, siglecs, galectins and chitinase-like lectins (Shen and Jacobs-Lorena, 1999; Dodd and Drickamer, 2001; Zaheer ul et al, 2007), among others. Each lectin family has characteristic carbohydrate-binding-fold consensus sequences, which differ greatly from one family to another.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous animal lectins are extremely diverse, and are organized into many families, including C-type, R-type, siglecs, galectins and chitinase-like lectins (Shen and Jacobs-Lorena, 1999; Dodd and Drickamer, 2001; Zaheer ul et al, 2007), among others. Each lectin family has characteristic carbohydrate-binding-fold consensus sequences, which differ greatly from one family to another.…”
Section: Discussionmentioning
confidence: 99%
“…A series of recent investigations into the X-ray structures and carbohydrate binding properties of SPX-40 family of chitolectins revealed that these proteins bind chitin-like oligosaccharides in a similar mode to the chitinases,[21, 22] within a groove with 9 subsites. [23, 24, 25, 26, 20] A key component of the sugar hydrolysis mechanism for Family 18 chitinases is known to be distortion of the N-acetylglucosamine ring at the binding site from a chair to a boat conformation. [27, 28, 21, 24, 29] However, although a similar distortion of a sugar ring to boat conformation has been seen to occur in the binding of chito-oligosaccharides to human cartilage glycoprotein[23], no commentary on possible ring distortions was made in three recent studies of related chitolectins.…”
Section: Resultsmentioning
confidence: 99%
“…[27, 28, 21, 24, 29] However, although a similar distortion of a sugar ring to boat conformation has been seen to occur in the binding of chito-oligosaccharides to human cartilage glycoprotein[23], no commentary on possible ring distortions was made in three recent studies of related chitolectins. [25, 26, 20]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the structural similarity between chito-oligosaccharides and the proteoglycan carbohydrate monomers, little evidence of polysaccharide binding beyond the original structural studies exists (10,11). In fact, we are aware of only one other study focusing on the molecular-level mechanism of carbohydrate binding in YKL-40 (19). From a bioinformatics and structural comparison of YKL-40 to a similar chi-lectin, mammary gland protein 40 (20), the authors propose an oligosaccharide binding mechanism that involves tryptophan-mediated gating of the primary carbohydrate binding site ( Fig.…”
mentioning
confidence: 99%